Robust Determinants of the Shadow Economy: An International Comparison - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2016)
To synthesize the literature on determinants of the shadow economy, this paper uses three cross-national shadow economy measures and employs numerous determinants over hundreds of model combinations to identify robust determinants of the shadow economy and address modeling uncertainty. We find that bureaucratic complexity is more significant than monetary severity in driving shadow activity. The incentives of new shadow entrepreneurs are somewhat different. A one standard deviation increase in tax complexity increases overall shadow economy by over ten percent of the mean. In contrast, a similar increase in business startup costs increases new informal entrepreneurs by almost more than double.
Keywords: M13; H26; K42; 330; shadow economy; robustness analysis; modeling uncertainty; entry barriers; development; taxes